Intra-amniotic inflammatory complications in preterm prelabor rupture of membranes and long-term neurodevelopmental outcomes of infants: a systematic review. (12th December 2022) - Burckova, Hana; Stranik, Jaroslav; Musilova, Ivana; Matulova, Jana; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective: To perform a systematic review of the literature available on the association between the presence of microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation and long-term neurodevelopmental outcomes of infants from pregnancies complicated by preterm prelabor rupture of membranes (PPROM). Methods: A literature search, from their earliest entries to May 2020, was performed by employing three electronic databases (Web of Science, PubMed, and Scopus). The selection criteria were as follows: (1) singleton pregnancies with PPROM; (2) available information regarding MIAC and/or intra-amniotic inflammation; (3) long-term (at least one year of the corrected age) neurodevelopmental outcomes of respective infants. Results: The initial search identified 10, 953 articles, of which 8 were selected for full-text reading; however, none were included in the review owing to the following reasons: (i) spontaneous preterm labor with intact membranes and/or indicated (iatrogenic) preterm delivery were included in the studies without providing separate data for PPROM ( n  = 5); (ii) long-term, at least one year of the corrected age, neurodevelopmental outcomes of infants were not assessed ( n  = 1); (iii) the presence of both the abovementioned reasons ( n  = 1); (iv) amniotic fluid was not assessed, and a long-term neurodevelopmental outcome was not evaluated ( n  = 1). Conclusion: The literature search provides evidence of a knowledge gap in the association between the presence of MIAC and/or intra-amniotic inflammation and long-term neurodevelopmental outcomes in infants with PPROM.